2022
DOI: 10.1038/s41467-022-33292-y
|View full text |Cite
|
Sign up to set email alerts
|

Helheim Glacier ice velocity variability responds to runoff and terminus position change at different timescales

Abstract: The Greenland Ice Sheet discharges ice to the ocean through hundreds of outlet glaciers. Recent acceleration of Greenland outlet glaciers has been linked to both oceanic and atmospheric drivers. Here, we leverage temporally dense observations, regional climate model output, and newly developed time series analysis tools to assess the most important forcings causing ice flow variability at one of the largest Greenland outlet glaciers, Helheim Glacier, from 2009 to 2017. We find that ice speed correlates most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 101 publications
0
13
1
Order By: Relevance
“…This is in some contrast to Ultee et al. (2022), who concluded that on seasonal timescales, Helheim was primarily runoff‐driven, and Bevan et al. (2015), who also found a link between runoff and seasonal surface elevation change.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…This is in some contrast to Ultee et al. (2022), who concluded that on seasonal timescales, Helheim was primarily runoff‐driven, and Bevan et al. (2015), who also found a link between runoff and seasonal surface elevation change.…”
Section: Discussioncontrasting
confidence: 69%
“…(2018) studied three points within 30 km of the terminus, while Ultee et al. (2022) studied 23 points at 1 km spacing on Helheim Glacier, and six points within ∼20 km of the terminus were analyzed at Jakobshavn Glacier by Joughin et al. (2012, 2019), at Helheim and Kangerdlussuaq Glaciers by Kehrl et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their analyses of Jakobshavn Isbrae, Joughin et al (2012) and Ashmore et al (2022) found that other processes contributes as well but to a smaller degree. For Helheim Glacier in southeast Greenland, Ultee et al (2022) concluded that both terminus position and runoff are important controls on the seasonal variations in flow. This is most likely the case for most glaciers and must be taken into account when interpreting the clusters.…”
Section: Discussionmentioning
confidence: 99%
“…For Helheim Glacier in southeast Greenland, Ultee et al. (2022) concluded that both terminus position and runoff are important controls on the seasonal variations in flow. This is most likely the case for most glaciers and must be taken into account when interpreting the clusters.…”
Section: Discussionmentioning
confidence: 99%